Advanced biorefinery feedstock from non-recyclable municipal solid waste by mechanical preprocessing - Saha, Nepu; Klinger, Jordan; Islam, Md Tahmid; Reza, Toufiq (Frontiers in Fuels, 2023)
Because of accelerated urbanization and development of global economy, a large quantity of municipal solid waste (MSW) has been collected and disposed of by the municipalities. Due to this drastic increase in the disposal of MSW, the need for its management is a must to preserve the environment. Currently, about 50% of the total MSW generated in the United States have been utilizing through various recycling, combustion, and composting technologies which means the remaining 50% is sent to landfill, often known as non-recyclable MSW (nMSW). As this nMSW is physically and chemically heterogenous and contains very high inorganics, processing is required prior using it as biorefinery feedstock. Thus, this study focused on how the mechanical preprocessing advanced the physical and chemical properties of nMSW. The physical and chemical properties were investigated in terms of particle size distribution, bulk density, ultimate and proximate analysis, and the higher heating value (HHV). The combustion properties were examined in terms of ignition temperature, peak heat release rate, and combustion efficiency. Results showed that the variability of physical and chemical properties of nMSW can be reduced by mechanical preprocessing. For example, the variability of the bulk density of the as received nMSW was about 17.3% while it reduced to 5.8% when sample was size reduced to 2 mm. Similarly, the variability of ash and HHV reduced from 49.2% to 11.0% and 13.4% to 4.2%, respectively. Combustion thermograms showed that the size reduction positively improves the combustion properties. For example, 2 mm on spec sample started to ignite about 4 times earlier as well as took 6.5 folds less time to reach the peak heating rate compared to as received nMSW. Overall, the mechanical preprocessing reduced the variability of physical and chemical properties in addition to the improvement of combustion behavior of the nMSW which are one step forward towards the biorefinery feedstock.